THE EFFECT OF HUMAN POWER EDUCATION AND DEVELOPMENT ON CORPORATE EFFICIENCY AND PERFORMANCE A THEORETICAL EVALUATION - GÜMÜŞ, Muhammet; ORHAN, Sibel; KIZILKAYA, Emine; MALTAŞ, Elif (Atlas Journal, 2021)
In this study, the effect of manpower training and development on organizational productivity was examined. The article observed that the efficiency and effectiveness of organizations mainly depend on the skills, attitudes, knowledge and competencies of their employees through training and development. The article stated that the main purpose of employee training and development is to develop the skills, knowledge and competencies of employees, which are vital for increasing organizational effectiveness, productivity, profitability, promoting and developing some competitive advantages over competitors. Training and development is based on the premise that employees’ attitudes, skills, behaviors, abilities and competencies should be developed in order to achieve organizational goals and objectives. The purpose, importance and some methods of the training and development of the employees and the factors affecting the training are discussed. Based on the review and discussion, conclusions and recommendations aimed at increasing organizational productivity and performance regarding employee training and development in organizations in Turkey are made.